Development of a Website-Based Cashier Application at the NBO Prabumulih Store Using the RAD Method - Lovita Reira Rambayu; Fajriyah; Khana wijaya (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
NBO Prabumulih Store is a store that sells various kinds of men's and women's clothing, NBO Prabumulih Store is located in North Prabumulih District, precisely in Anak Petai Village. Currently, NBO Prabumulih Store does not have a cashier application for managing payment transactions, so the purpose of this study is to build a cashier application to facilitate payment transactions at NBO Prabumulih Store. This research method uses a qualitative descriptive method with data collection techniques in the form of observation, interviews and literature studies, data sources consist of primary data and secondary data, while for the system development method using the RAD (Rapid Application Development) method, the system design tool used is UML (Unified Modeling Language). The design of this application uses the PHP (Processor Hypertext) programming language, MySQL Database and Coding using Visual Studio Code